Anwara Syed Haque's fiction: Women's uprising and observation/ আনোয়ারা সৈয়দ হকের কথাসাহিত্য : নারী বিদ্রোহ ও পর্যবেক্ষণ (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
There is scrutinized observation of contemporary women and society in Anwara Syed Haque's literary work. It is perfectly mingled united in fiction. Her narratives skillfully intertwine feminist perspectives with the concept of rebellion, presenting it in a contextually relevant and renewed form. Because the root crisis of social degradation is the humiliation of women and the social deprivation. Even, to represent and consider women in a different way is the patriarchal vision. In recent scenario, there are unrestricted conflicts and lacks between men and women. developments, there is a visible and unrestricted conflict between men and women. There are ingrained patriarchy, carnal thinking, and regressive traditions. Even state agents, republic officials, and so-called progressive individuals are not moderate, rather, they take women for consuming goods. They are not acknowledged equally; even, they will be capable of keeping contributions if the access to work and a conducive environment are assured, but, to subdue is the fairest conclusion so that they can never be rebellious because the existing material structure will be broken down if they rise their voices. In this case, various material and moral restrictions are being systematically imposed upon women that are counted as two ways of getting redemption from the men's lust. There is multiple shortages of confidence and fidelity of the men to the working and laboring women in the country. Men attempt to disgrace women in multiple ways, often using fear— both worldly and spiritual. Out of fear of women becoming equal partners, efforts are made to push them back. Yet, if women are allowed equal footing and presence, both domestic and social spheres could experience genuine social and economic liberation. Both rural and urban societies are now under the pressure of foreign ideologies, distorting local cultural perspectives and promoting indecent views of women. The foundation of society is human. Human-centric polarization is inherently relative. If women become courageous and aware, it would challenge the very audacity to produce obscene media or perpetuate exploitation; the rebellion of women is the demand of the time. Feminist thought and rebellion are real commentary in her literature, presenting the events that awakened women's society in which the unprotected lives of many women have been outlined. The rebellious thought and the real scenario of the women society are held  by illustrating the complete fiction.
Keywords: Contribution of women; Student politics; Sunset law; Chromosome; Religious belief; Racticing modesty; Rights